Impacted urethral stones in an eleven years old girl: A case report - Mahwish Noor-ul-haq; Zafar, Zuha; Yousaf, Abdullah; Shahzad, Babar; Waheed, Muhammad Rehman; Fatima, Batool (Journal of the Pakistan Medical Association, 2026)
Although urolithiasis is relatively common, urethral stones are rare, with an incidence of less than 0.3%. They are particularly uncommon in children, occurring 20 times less frequently than in adults, and are rarely seen in females as compared to males. The presence of an obstructing urethral stone resulting in acute urinary retention constitutes a urological emergency and requires immediate intervention. We present an unusual case of impacted urethral stones in a female child who presented to the Paediatric surgery emergency department at Mayo hospital, Lahore on 22nd October 2024. The diagnosis was established based on clinical history and examination, and the stones were retrieved under general anaesthesia. Further evaluation identified no underlying metabolic or anatomical abnormalities, suggesting that the stones originated from the primary urinary source. This case underscores the importance of considering urethral stones in the differential diagnosis of paediatric urinary tract obstruction, despite its rarity. Keywords: Female urethral calculi, acute urinary retention, urologic emergency.